Assessment of Interleukin-12, Gamma Interferon, and Tumor Necrosis Factor Alpha Secretion in Sera from Mice Fed with Dietary Lipids during Different Stages of Listeria monocytogenes Infection - Puertollano, María A. (American Society for Microbiology, 2005)
Recent experimental observations have determined that long-chain n-3 polyunsaturated fatty acids suppress immune functions and are involved in the reduction of infectious disease resistance. BALB/c mice were fed for 4 weeks with one of four diets containing either olive oil (OO), fish oil (FO), hydrogenated coconut oil, or a low fat level. Interleukin-12p70 (IL-12p70), gamma interferon (IFN-γ), and tumor necrosis factor alpha (TNF-α) production in the sera of mice fed these diets and challenged with Listeria monocytogenes were determined by enzyme-linked immunosorbent assay. In addition, bacterial counts from spleens of mice were carried out at 24, 72, or 96 h of infection. Here, we quantified an initial diminution of production of both IL-12p70 and IFN-γ, which appear to play an important role in the reduction of host resistance to L. monocytogenes infection. In addition, an efficient elimination of L. monocytogenes was observed in spleens of mice fed a diet containing OO at 96 h of infection, despite reductions in IL-12p70 and TNF-α production, suggesting an improvement of immune resistance. Overall, our results indicate that the initial reduction of both IL-12 and IFN-γ production before L. monocytogenes infection represents the most relevant event that corroborates the impairment of immune resistance by n-3 polyunsaturated fatty acids during the different stages of infection. However, we speculate that the modulation of other cytokines must be also involved in this response, because the alteration of cytokine production in mice fed an FO diet in a late phase of L. monocytogenes infection was similar to that in mice fed OO, whereas the ability to eliminate this bacterium from the spleen was improved in the latter group.